ARTICLE REVIEW: UTILIZATION OF CURCUMIN AS AN ANTI-CANCER AGENT - Abdul Mulki Irpani; Deden Indra Dinata; Garnadi Jafar (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
The uncontrolled growth of abnormal cells in one area of the body can spread to other tissues and create more cancer cells, a disease known as cancer. Malignant cancer cells have the potential to become fatal. After cardiovascular disease, cancer is the second most common cause of mortality. Numerous cancer types exist, including stomach, liver, colorectal, lung, breast, and cervical cancers. More than 70% of cancer-related deaths occur in low- and middle-income nations, and the number of cancer-related deaths is predicted to rise steadily, hitting 11.5 million by 2030. Some of the resources utilized to look up information on curcumin's application as an anticancer agent are PubMed, Science Direct, and Google Scholar. Most of the articles that were used were published between 2013 and 2023, or within the last ten years. These journals were found using the following keywords: "Curcumin," "Cancer," "Curcumin as an Anticancer," and "Utilization of Curcumin as an Anticancer Agent." Scholars from many nations have conducted comparable investigations on the application of curcumin as an anticancer agent. Furthermore, it has been established that curcumin directly inhibits cancer cells when used as an anticancer drug. This suggests that curcumin does have anticancer properties. Keywords: Curcumin, Cancer, Curcumin as an Anticancer agent